Warlord of Kor - Carr, Terry, 1937-1987 (Salt Lake City, UT : Project Gutenberg, 2006)
"Warlord of Kor" by Terry Carr is a science fiction novel written in the early 1960s. The book centers around Lee Rynason, an Earthman working as part of a survey team on the alien planet of Hirlaj, where he interacts with the telepathic Hirlaji race. The storyline unfolds around their rich history, with pivotal insights shared by Horng, a Hirlaji, about their past and their god-like figure, Kor, raising questions about survival and the looming threat of other intelligent species. The opening of the novel introduces a tense examination of the Hirlaji civilization through Rynason's interactions with Horng, which reveal their long, dormant memories and a destructive legacy. As Rynason interviews Horng, he learns about a significant historical figure, Tebron, and his transformation of Hirlaj into a peaceful society after a violent past. The narrative hints at Kor being both a god and a machine, representing the knowledge sought by the Hirlaji. With rising concerns about the potential for imminent conflict spurred by the ambitious head of Rynason's team, Manning, the initial chapter sets up a stark juxtaposition between the tranquil Hirlaji culture and the disruptive intentions of the human settlers. (This is an automatically generated summary.)
Release date is 2006-03-10
Greg Weeks, Barbara Tozier, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Science fiction